Paralenaeus (Hemiptera: Reduviidae: Reduviinae) found in China with the description of the second species of the genus - Yang, Hailin; Cao, Liangming; Cai, Waizhi (Zootaxa, 2012)
The genus Paralenaeus Reuter, 1881, is recorded for the first time from China. The second species of the genus, Parale-naeus schaeferi sp. n., is described from Yunnan. Dorsal habitus, male genitalia, and other diagnostic morphological characters of the new species are illustrated.